Las guerras de los niǫs republicanos : (1936-1995) / Eduardo Pons Prades ; prólogo Eduardo Haro Tecglen ; epílogo Paco Lobatón - Haro Tecglen, Eduardo (1924-2005) Lobatón, Paco; Pons Prades, Eduardo (1920-2007)
Bibliografía. Índice